Peranan Trichoderma terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine Max) pada Kondisi Cekaman Kekeringan - Desi Kartika Sutrisno; Sri Hartatik; Parawita Dewanti (Kadiri University, 2022)
The increase of soybean (Glycine max) production, particularly in the drought-stricken areas, can be done by improving cultivation techniques. Trichoderma sp. fungus is expected to increase the efficiency of the root function of soybean plants in absorbing water, especially in drought conditions. This experiment aimed to examine the effect of drought stress levels with different Trichoderma sp. applications on the growth and yield of soybeans. The experiment was carried out in a plastic house using a two-factorials Completely Randomized Design (CRD). The first factor was the administration of Trichoderma harzianum with four dosage levels, namely T0 (0 grams), T1 (20 grams), T2 (40 grams), and T3 (60 grams). The second factor was three drought stress levels, namely C1 (40%KL), C2 (60%KL), and C3 (80%KL). Data analysis employed the analysis of variance and follow-up test of DMRT at 5% level if there was an interaction between the two treatment factors. Observation variables included plant height, root length, number of flowers, number of productive branches, proline, root wet weight, the weight of biomass, number of effective root nodules, relative growth rate, number of pods, number of pithy pods, number of empty pods, pod weight, and seed weight. The results implied that the effect of the tested drought stress level was still tolerant at 60% KL with the application of Trichoderma sp. at a dose of 40 grams. There was an interaction between the effect of dosage of Trichoderma sp. and drought stress level on plant height and root length and proline content and biomass weight of soybean plants at 81 DAP. Peningkatan produksi kedelai utamanya pada lahan tercekam kekeringan dapat dilakukan melalui perbaikan teknik budidaya. Pemanfaatanjamur Trichodermasp. diharapkan dapat meningkatkan efisiensi fungsi perakaran tanaman kedelai dalam menyerap air khususnya pada kondisi kekeringan. Percobaan ini bertujuan untuk mengkaji pengaruh tingkat cekaman kekeringan dengan aplikasi Trichodermasp. yang berbeda terhadap pertumbuhan dan hasil tanaman kedelai. Percobaan dilakukan di rumah plastik dengan menggunakan Rancangan Acak Lengkap (RAL) faktorial dengan dua faktor, faktor pertama pemberian dosis Trichoderma harzianum dengan empat taraf: T0 (0 gram), T1 (20 gram), T2 (40 gram), dan T3 (60 gram) dan faktor kedua tingkat cekaman kekeringan dengan tiga taraf: C1 (40%KL), C2 (60%KL) dan C3 (80%KL). Analisa data menggunakan analisis sidik ragam dan uji lanjut DMRT Taraf 5% jika terdapat interaksi pada dua faktor perlakuan. Variabel pengamatan meliputi tinggi tanaman, panjang akar, jumlah bunga, jumlah cabang produktif, prolin, berat basah akar, berat biomassa, jumlah bintil akar efektif, laju pertumbuhan relatif, jumlah polong, jumlah polong bernas, jumlah polong hampa, berat polong dan berat biji. Hasil percobaan menunjukkan pengaruh tingkat cekaman kekeringan yang diujikan masih toleran pada 60% KL dengan aplikasi Trichodermasp. pada dosis 40gram. Terdapat interaksi antara pengaruh dosisTrichodermasp. dan cekaman kekeringan terhadap tinggi tanaman dan panjang akar serta kandungan prolin dan berat biomassa tanaman kedelai pada umur 81 HST.